Prescribed Renoprotective Chinese Herbal Medicines Were Associated with a Lower Risk of All-Cause and Disease-Specific Mortality among Patients with Chronic Kidney Disease: A Population-Based Follow-Up Study in Taiwan. (17th July 2017) - Hsieh, Chuan-Fa; Chang, Huan-Cheng; Huang, Song-Lih; Chen, Chien-Lung; Chen, Wei-Ta; Yang, Chen-Chang
Abstract : Chinese herbal medicines (CHMs) containing aristolochic acid (AA) are associated with chronic kidney disease (CKD), but some prescribed CHMs have been shown to possess renoprotective effects. We conducted a nationwide retrospective cohort study to delineate the role of prescribed CHMs on the CKD progression. Renoprotective CHM (RPCHM) was defined if a CHM contained dong chong xia cao ( Cordyceps sinensis (Berk.) Sacc.), da huang ( Rheum palmatum L), huang qi (Astragalus membranaceus), dan shen ( Salvia miltiorrhiza Bge.), and dong quai ( Angelica sinensis (Oliv.) Diels) or belonged to specific mixture herbal formulations (Yishen capsule, Saireito, or Wen Pi Tang). Subjects who had ever used AA-containing CHMs, had cancer or HIV prior to CKD diagnosis, or died within the first month of CKD diagnosis were excluded. A total of 11, 625 patients were eligible subjects. The adjusted hazard ratio (aHR) for all-cause mortality was 0.6 ( p < 0.001) and 0.6 ( p = 0.013) among subjects receiving RPCHMs containing Angelica sinensis and those receiving other RPCHMs, respectively. For CKD-related mortality, the aHR among subjects receiving RPCHMs containing Angelica sinensis was 0.6 (p = 0.025). The use of specific RPCHMs, especially those that contained Angelica sinensis, was associated with a lower risk of mortality among CKD patients.